Nerve‐sparing radical hysterectomy compared to standard radical hysterectomy for women with early stage cervical cancer (stage Ia2 to IIa) - Kietpeerakool, Chumnan (Cochrane Database Syst Rev, 2019)
BACKGROUND: Radical hysterectomy is one of the standard treatments for stage Ia2 to IIa cervical cancer. Bladder dysfunction caused by disruption of the pelvic autonomic nerves is a common complication following standard radical hysterectomy and can affect quality of life significantly. Nerve‐sparing radical hysterectomy is a modified radical hysterectomy, developed to permit resection of oncologically relevant tissues surrounding the cervical lesion, while preserving the pelvic autonomic nerves. OBJECTIVES: To evaluate the benefits and harms of nerve‐sparing radical hysterectomy in women with stage Ia2 to IIa cervical cancer. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL; 2018, Issue 4), MEDLINE via Ovid (1946 to May week 2, 2018), and Embase via Ovid (1980 to 2018, week 21). We also checked registers of clinical trials, grey literature, reports of conferences, citation lists of included studies, and key textbooks for potentially relevant studies. SELECTION CRITERIA: We included randomised controlled trials (RCTs) evaluating the efficacy and safety of nerve‐sparing radical hysterectomy compared to standard radical hysterectomy for women with early stage cervical cancer (stage Ia2 to IIa). DATA COLLECTION AND ANALYSIS: We applied standard Cochrane methodology for data collection and analysis. Two review authors independently selected potentially relevant RCTs, extracted data, evaluated risk of bias of the included studies, compared results and resolved disagreements by discussion or consultation with a third review author, and assessed the certainty of evidence. MAIN RESULTS: We identified 1332 records as a result of the search (excluding duplicates). Of the 26 studies that potentially met the review criteria, we included four studies involving 205 women; most of the trials had unclear risks of bias. We identified one ongoing trial. The analysis of overall survival was not feasible, as there were no deaths reported among women allocated to standard radical hysterectomy. However, there were two deaths in among women allocated to the nerve‐sparing technique. None of the included studies reported rates of intermittent self‐catheterisation over one month following surgery. We could not analyse the relative effect of the two surgical techniques on quality of life due to inconsistent data reported. Nerve‐sparing radical hysterectomy reduced postoperative bladder dysfunctions in terms of a shorter time to postvoid residual volume of urine ≤ 50 mL (mean difference (MD) ‐13.21 days; 95% confidence interval (CI) ‐24.02 to ‐2.41; 111 women; 2 studies; low‐certainty evidence) and lower volume of postvoid residual urine measured one month following operation (MD ‐9.59 days; 95% CI ‐16.28 to ‐2.90; 58 women; 2 study; low‐certainty evidence). There were no clear differences in terms of perioperative complications (RR 0.55; 95% CI 0.24 to 1.26; 180 women; 3 studies; low‐certainty evidence) and disease‐free survival (HR 0.63; 95% CI 0.00 to 106.95; 86 women; one study; very low‐certainty evidence) between the comparison groups. AUTHORS' CONCLUSIONS: Nerve‐sparing radical hysterectomy may lessen the risk of postoperative bladder dysfunction compared to the standard technique, but the certainty of this evidence is low. The very low‐certainty evidence for disease‐free survival and lack of information for overall survival indicate that the oncological safety of nerve‐sparing radical hysterectomy for women with early stage cervical cancer remains unclear. Further large, high‐quality RCTs are required to determine, if clinically meaningful differences of survival exist between these two surgical treatments.